2012
DOI: 10.1111/j.1601-6343.2012.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights on age‐related association between nasopharyngeal airway clearance and facial morphology

Abstract: Airway measurements were smallest in children ≤ 6 years and those presenting severe hyperdivergent pattern, which denoted the most severe airway obstruction. The findings suggest airway clearance before age 6 in the most severely affected children, but follow-up research on actual adenoidectomies in younger children is needed to determine guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…Except for gender differences in group H, our findings are concurrent with those of other studies 17,18 that found thicker soft tissue in all aspects of the face in men compared with women. The exception in group H might be related to the similar effect of the STC reduction in subjects with the most hyperdivergence and increased lower face height; this hypothesis is discussed later in the context of differential growth between hard and soft tissues.…”
Section: Gender Differencessupporting
confidence: 83%
“…Except for gender differences in group H, our findings are concurrent with those of other studies 17,18 that found thicker soft tissue in all aspects of the face in men compared with women. The exception in group H might be related to the similar effect of the STC reduction in subjects with the most hyperdivergence and increased lower face height; this hypothesis is discussed later in the context of differential growth between hard and soft tissues.…”
Section: Gender Differencessupporting
confidence: 83%
“…[16,21] After children developed mixed dentition, it was more unlikely to get a spontaneous dentition correction following surgery. [31] In terms of relapse, 1 study reported that snoring and mouth-breathing tended to relapse after surgery. [15] The relapse was due to the habit of open-mouth posture, regrowth of adenoid tissue, and primary craniofacial deformity.…”
Section: Discussionmentioning
confidence: 99%
“…En niños en crecimiento, una infección puede causar hipertrofia de este tejido y, por consiguiente, constricción de la vía aérea (8). Existe abundante literatura que seña-la que la presencia de estas estructuras disminuye el diámetro naso y orofaríngeo y produce síntomas como ronquidos y respiración bucal crónica (16)(17)(18)(19).…”
Section: Discussionunclassified